2020
DOI: 10.1371/journal.pone.0231626
|View full text |Cite
|
Sign up to set email alerts
|

DeepDetectNet vs RLAttackNet: An adversarial method to improve deep learning-based static malware detection model

Abstract: Deep learning methods are being increasingly widely used in static malware detection field because they can summarize the feature of malware and its variants that have never appeared before. But similar to the picture recognition model, the static malware detection model based on deep learning is also vulnerable to the interference of adversarial samples. When the input feature vectors of the malware detection model is based on static features of Windows PE (Portable Executable, PE) file, the model is vulnerab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“… Nasiri, Khosravani & Weinberg (2017) noted that artificial neural networks (ANNs) have been used to detect faults in the rotor system of helicopters and can predict crack growth for sheet material. Fang et al (2020) reported on the use of deep learning in malware detection that achieves better results with a high effectiveness. Moreover, feature extraction for malware detection performs better with deep learning ( Fang et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… Nasiri, Khosravani & Weinberg (2017) noted that artificial neural networks (ANNs) have been used to detect faults in the rotor system of helicopters and can predict crack growth for sheet material. Fang et al (2020) reported on the use of deep learning in malware detection that achieves better results with a high effectiveness. Moreover, feature extraction for malware detection performs better with deep learning ( Fang et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“… Fang et al (2020) reported on the use of deep learning in malware detection that achieves better results with a high effectiveness. Moreover, feature extraction for malware detection performs better with deep learning ( Fang et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…On the basis of gym-malware, there are multiple follow-up work [20,39,41,42,72,76,139] proposing problem-space black-box adversarial attacks against static PE malware detection models.…”
Section: 22mentioning
confidence: 99%
“…1) DQEAF uses a subset of modifications employed in gym-malware and guarantees that all of them would not lead to corruptions in the modified malware; 2) DQEAF uses a vector with 513 dimensions as the observed state, which is much lower than that in gym-malware; 3) DQEAF makes the priority into consideration during the replay of past transitions. Fang et al [41] also observe that the modifications in the action space of gym-malware have some randomness and further found that most effective adversarial malware from gymmalware are generated by UPX pack/unpacked modifications, which could lead to some training problems with RL due to the non-repeatability of those modifications. Thus, they first reduce the action space to 6 categories having certain deterministic parameters and then propose an improved black-box adversarial attack, namely RLAttackNet, based on the gym-malware implementation.…”
Section: 22mentioning
confidence: 99%
“…Machine learning algorithms are developed to assume that the environment is benign, but they fail when even a small adversary can modify their inputs. This is where adversarial machines come in handy [42]. Adversarial machine learning is a branch of machine learning that studies a set of assaults aimed at degrading the performance of classifiers on certain tasks.…”
Section: Adversarial Machine Learningmentioning
confidence: 99%